Seeing Halley's Comet at Vista Point 1689 Auberry Road, Auberry - Watkins, Howard::::::::: (1986)
Front: Adam Watkins, Josiah Gordon and Jared Gordon; Back: Howard Watkins and Dean Gordon All wearing warm jackets and head covers